A natural cellulose modified degradable oxygen barrier breathable membrane and preparation method thereof
By blending modified PLA and modified natural cellulose, and adding additives such as cerium complex and polydopamine, a degradable oxygen-resistance breathable film with good tear resistance, antibacterial properties and cost-controllable, solving the shortcomings of the existing food packaging film in terms of oxygen resistance, breathability and degradability.
Patent Information
- Application Number
- CN202410847293.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-06-27
AI Technical Summary
The existing food packaging films have shortcomings in oxygen resistance, breathability and degradability, and are costly, making it difficult to widely use in the field of packaging materials.
By blending modified PLA and modified natural cellulose, and adding additives such as cerium complex and polydopamine, a degradable oxygen-resistance breathable membrane with good tear resistance, antibacterial properties and controllable cost is prepared.
The PLA film has been improved with improved antibacterial performance, enhanced oxygen resistance and tear resistance, while reducing production costs, forming a high-performance degradable film suitable for food packaging.
Smart Images

Figure BDA0004916007410000091 
Figure BDA0004916007410000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of degradable packaging materials, and in particular to a natural cellulose-modified degradable oxygen-barrier breathable film and a preparation method thereof. Background Art
[0002] In recent years, with the development of economy, people's requirements for food quality are getting higher and higher, and the development of food packaging materials has also received people's attention. Food packaging materials are mainly used to package fruits, vegetables, fresh meat and other foods, and need to have oxygen barrier and air permeability. Oxygen barrier and air permeability can make the packaging film reduce the entry of oxygen while ensuring the moisture in the film, inhibiting the growth of microorganisms and inhibiting enzyme activity to prevent the oxidation and deterioration of fats and proteins. However, most of the food packaging films currently used are made of PE and PP materials. A large amount of discarded packaging films are easy to pollute the soil. Therefore, the development of degradable food packaging films is of great significance to protecting the environment.
[0003] Among biodegradable materials, polylactic acid (PLA) is made from lactic acid fermented from plants. It has excellent biocompatibility and good mechanical properties, and is non-toxic, highly plastic and completely biodegradable. However, PLA is easy to crystallize, which makes its elasticity, flexibility and impact resistance poor, greatly limiting its application in the field of packaging materials.
[0004] Natural cellulose is a macromolecular polysaccharide composed of glucose. It is the main component of plant cell walls and is the most widely distributed and abundant in nature. Adding it to PLA can enhance the strength of PLA film. However, natural cellulose has many hydroxyl groups on its surface, making it less compatible with PLA, so it needs to be modified.
[0005] Patent CN112552655A discloses a modified cellulose-filled PBAT / PLA composition suitable for preparing a film, and its preparation and application. Hydroxyethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, and cellulose acetate butyrate sold on the market are used as modified celluloses and blended with PBAT, PLA and a compatibilizer, a plasticizer, a chain extender, and a lubricant to prepare a biodegradable film with low cost and good mechanical properties. However, these modified celluloses still have a large number of hydroxyl groups, and the compatibilizer alone cannot ensure that the modified cellulose is evenly dispersed in PLA.
[0006] Patent CN111825845B discloses a polylactic acid grafted modified natural fiber and PLA composite material and its preparation method, which comprises mixing functional natural fiber, functional polylactic acid and solvent, adding initiator, and performing click chemistry reaction. This method can effectively improve the interface between the two phases, and is simple and easy to implement, suitable for industrial production; the prepared natural fiber / polylactic acid composite material and composite fiber have better breaking strength, impact strength and heat resistance, but the cost of click chemistry reaction is relatively high.
[0007] Therefore, there is an urgent need in the market for a natural cellulose-modified biodegradable oxygen-barrier breathable membrane with good tear resistance, antibacterial properties and controllable costs. Summary of the invention
[0008] In view of the problems existing in the prior art, the object of the present invention is to obtain a natural cellulose-modified degradable oxygen-barrier breathable membrane with good tear resistance and antibacterial properties.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] On one hand, the present invention provides a natural cellulose modified degradable oxygen barrier breathable membrane, which comprises the following raw materials in parts by weight: 50-70 parts of modified PLA, 10-15 parts of modified natural cellulose, 1-2 parts of plasticizer, 2-5 parts of compatibilizer, and 0.1-2 parts of lubricant.
[0011] The present application improves the antibacterial properties of PLA film by modifying PLA, blending it with natural cellulose and adding various additives to improve the problems of PLA's high brittleness, low strength and poor toughness, thereby obtaining a natural cellulose-modified biodegradable oxygen-barrier breathable film with good tear resistance, antibacterial properties and controllable costs.
[0012] In some embodiments, the method for preparing the modified PLA comprises the following steps:
[0013] A1. Dissolve cerium nitrate in deionized water in a reaction vessel, then add a complexing agent, react at 30-40° C. for 3-5 hours, add 20-28 wt % ammonia water to adjust the pH to 7-8, let stand for 8-12 hours, centrifuge, filter, and dry to obtain a cerium complex;
[0014] A2. Add the cerium complex obtained in step A1, lactic acid and solvent into a reaction vessel, react at 130-150° C. for 1-3 h, and then evacuate for 3-5 h with a vacuum degree of 0-0.1 MPa. After drying, obtain modified PLA.
[0015] Preferably, the preparation method of the modified PLA comprises the following steps:
[0016] A1. Dissolve cerium nitrate in deionized water in a reaction vessel, wherein the mass ratio of cerium nitrate to deionized water is 1:(1.5-2), then add a complexing agent, wherein the mass ratio of cerium nitrate to complexing agent is 1:(3-5), react at 30-40° C. for 3-5 hours, add 20-28 wt % ammonia water to adjust the pH to 7-8, stand for 8-12 hours, centrifuge, filter, and dry to obtain a cerium complex;
[0017] A2. Add the cerium complex obtained in step A1, lactic acid and toluene into a reaction vessel, wherein the mass ratio of the cerium complex to toluene is 1:(4-6), react at 130-150° C. for 1-3 h, then evacuate for 3-5 h, with a vacuum degree of 0-0.1 MPa, and obtain modified PLA after drying.
[0018] In the present application, cerium nitrate and a ligand are reacted to obtain a cerium complex, which is polymerized with a lactic acid monomer to obtain a modified PLA. On the one hand, the problem that conventional cerium modifiers are poorly dispersed and easily agglomerated in PLA is solved; on the other hand, after the organic ligand forms a complex with cerium, part of the electrons on the cerium are transferred to the organic ligand, resulting in a delocalization effect, which reduces the polarity of the cerium ion, thereby making the complex fat-soluble, and can better penetrate biological cell membranes, affecting the cell metabolism of microorganisms, thereby improving the antibacterial properties of the PLA film, and the cerium distributed between the PLA segments can coordinate with the oxygen in the PLA film, thereby improving the oxygen barrier performance of the PLA film.
[0019] In some embodiments, the complexing agent is one or more of monosodium citrate, monosodium malate, and sodium hydrogen tartrate.
[0020] Preferably, the complexing agent is monosodium citrate.
[0021] The applicant preferably uses monosodium citrate as the organic ligand of cerium ions. On the one hand, the three carboxyl groups on citric acid have a strong coordination ability with cerium ions, so that the cerium complex has the best antibacterial effect; on the other hand, the remaining two carboxyl groups and one hydroxyl group on the cerium complex can participate in the polymerization reaction of lactic acid, which not only ensures the compatibility of the cerium complex with the PLA segment but also allows cross-linking between the PLA segments, further improving the density of the PLA molecules, and can improve the barrier effect of PLA to oxygen and the tear resistance of the PLA film.
[0022] In some embodiments, the mass ratio of the cerium complex to lactic acid in step A2 is 1:(7-9).
[0023] By selecting a cerium complex with a specific ratio as a modifier for polylactic acid, the applicant can make the cerium complex chain segments evenly distributed on the polylactic acid chain segments, which can destroy the regularity of the polylactic acid chain segments and is not likely to affect the biodegradability of the polylactic acid.
[0024] In some embodiments, the method for preparing the modified natural cellulose comprises the following steps:
[0025] B1, adding natural cellulose, isophorone diisocyanate and organic bismuth into a reaction vessel, reacting at 70-80° C. for 3-5 hours to obtain activated natural cellulose;
[0026] B2. Add the activated natural cellulose and dopamine obtained in step B1 to a reaction vessel, react at 30-40° C. for 1-2 hours, add tris(hydroxymethyl)aminomethane buffer with a pH of 8-9, stir for 20-24 hours, wash the obtained product with deionized water to a pH of 7-8, filter and dry to obtain modified natural cellulose.
[0027] Preferably, the method for preparing the modified natural cellulose comprises the following steps:
[0028] B1, adding natural cellulose, isophorone diisocyanate and organic bismuth into a reaction vessel, wherein the mass ratio of natural cellulose to isophorone diisocyanate is 1:(2-3), and reacting at 70-80° C. for 3-5 hours to obtain activated natural cellulose;
[0029] B2. Add the activated natural cellulose and dopamine obtained in step B1 to a reaction vessel, react at 30-40° C. for 1-2 hours, add tris(hydroxymethyl)aminomethane buffer with a pH of 8-9, wherein the mass ratio of tris(hydroxymethyl)aminomethane buffer to activated natural cellulose is 1:(4-6), stir for 20-24 hours, wash the obtained product with deionized water to a pH of 7-8, filter and dry to obtain modified natural cellulose.
[0030] The applicant selected isophorone diisocyanate to activate natural cellulose. On the one hand, the isocyanate group reacts with the hydroxyl group on the natural cellulose to introduce a long alkyl chain segment on the natural cellulose, solving the problem of poor dispersibility of natural cellulose in PLA; on the other hand, the introduction of isocyanate groups on natural cellulose enhances the reactivity of natural cellulose, allowing it to react with the amino group on dopamine. Dopamine on natural cellulose undergoes self-polymerization under alkaline conditions to form polydopamine with viscosity. On the one hand, the viscosity of polydopamine is conducive to the compatibility of natural cellulose with PLA; on the other hand, polydopamine contains a large amount of catechol, which can transfer electrons through phenolquinone isomerism and destroy bacterial cell walls through catechol chelated ions of polydopamine. At the same time, natural cellulose acts as an intermediate medium to connect the cerium complex and polydopamine dual bactericidal substances to play a synergistic role, increase the activity of the antibacterial material, and enhance the antibacterial ability of the PLA film.
[0031] In some embodiments, the mass ratio of the activated natural cellulose to dopamine in step B2 is (15-25):1.
[0032] The present application selects dopamine in a specific ratio as a modifier for activated cellulose, which can make the performance of each part of the PLA film more stable. This may be because polydopamine can have a suitable chain segment length, does not cause cellulose to agglomerate, and makes it evenly dispersed in PLA.
[0033] In some embodiments, the natural cellulose is one or more of bamboo fiber, hemp fiber, microcrystalline cellulose, cellulose nanocrystal, and wool.
[0034] Preferably, the natural cellulose is cellulose nanocrystals.
[0035] In some embodiments, the plasticizer is one or more of epoxy fatty acid, epoxy soybean oil, citrate, polyethylene glycol, and castor oil derived ester.
[0036] Preferably, the plasticizer is epoxidized soybean oil.
[0037] In some embodiments, the compatibilizer is one or more of maleic anhydride grafted polyolefin, maleic anhydride grafted styrene-butadiene block copolymer, maleic anhydride grafted acrylonitrile-styrene-butadiene copolymer, and styrene-maleic anhydride-acrylonitrile copolymer.
[0038] Preferably, the compatibilizer is styrene-maleic anhydride-acrylonitrile copolymer.
[0039] In some embodiments, the lubricant is pentaerythritol stearate or ethylene bisstearamide.
[0040] Preferably, the lubricant is ethylene bisstearamide.
[0041] Another aspect of the present invention provides a method for preparing a natural cellulose-modified degradable oxygen-barrier breathable membrane, comprising the following steps:
[0042] S1. After mixing modified PLA, modified natural cellulose, plasticizer, compatibilizer and lubricant, add them into a high-speed mixer and mix for 20-30 minutes to obtain a premix;
[0043] S2, putting the premix obtained in step S1 into a twin-screw extruder, and controlling the extrusion temperature at 170-190° C. to obtain a film blowing masterbatch;
[0044] S3. The film blowing masterbatch obtained in step S2 is blown into a film by a film blowing machine, the screw temperature is controlled at 160-170° C., the die processing temperature is controlled at 170-180° C., and the film thickness is controlled at 25-50 μm to obtain a natural cellulose modified degradable oxygen-barrier breathable film.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The present invention improves the antibacterial properties of PLA film by modifying PLA and blending it with natural cellulose and adding various additives to improve the problems of PLA's high brittleness, low strength and poor toughness, thereby obtaining a natural cellulose-modified biodegradable oxygen-barrier breathable film with good tear resistance, antibacterial properties and controllable costs.
[0047] (2) The present invention polymerizes the prepared cerium complex with lactic acid monomer to obtain modified PLA, which solves the problem that conventional cerium modifiers have poor dispersibility and are easy to agglomerate in PLA. On the other hand, it improves the antibacterial properties of the PLA film. In addition, the cerium distributed between the PLA segments can coordinate with the oxygen in the PLA film, thereby improving the oxygen barrier properties of the PLA film.
[0048] (3) The present invention uses monosodium citrate as the organic ligand of cerium ions. On the one hand, the three carboxyl groups on citric acid have a strong coordination ability with cerium ions, so that the complex has the best antibacterial effect; on the other hand, the remaining two carboxyl groups and one hydroxyl group on the complex can participate in the polymerization reaction of lactic acid, which not only ensures the compatibility of the cerium complex with the PLA segment but also allows cross-linking between the PLA segments, further improving the density of the PLA molecules, and can improve the barrier effect of PLA to oxygen and the tear resistance of the PLA film.
[0049] (4) The present invention uses isophorone diisocyanate to activate natural cellulose, which on the one hand solves the problem of poor dispersibility of natural cellulose in PLA; on the other hand, it enhances the reactivity of natural cellulose so that it can react with the amino group on dopamine. The dopamine on the natural cellulose can undergo self-polymerization under alkaline conditions to form polydopamine with viscosity, which on the one hand is beneficial to the compatibility of natural cellulose and PLA; on the other hand, polydopamine can destroy bacterial cell walls. At the same time, natural cellulose acts as an intermediate medium to connect the cerium complex and polydopamine dual bactericidal substances to exert a synergistic effect, thereby increasing the activity of the antibacterial material and improving the antibacterial ability of the PLA film. DETAILED DESCRIPTION
[0050] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0051] In the following examples and comparative examples, except for modified PLA and modified natural cellulose, the other compounds and related reagents used can be purchased from the market. The cellulose nanocrystals have a width of 1-20 nm and a length of 200-800 nm, which were purchased from Zhejiang Jinjiahao Green Nanomaterials; the styrene-maleic anhydride-acrylonitrile copolymer model is SAM-010, which was purchased from Jiayirong Polymer (Shanghai) Co., Ltd.
[0052] Preparation Example 1
[0053] The preparation method of modified PLA-1 comprises the following steps:
[0054] A1. Dissolve 1 g of cerium nitrate in 8.75 g of deionized water in a reaction container, then add 4 g of monosodium citrate, react at 35° C. for 4 h, add 25 wt % of ammonia water to adjust the pH to 7, let stand for 10 h, centrifuge, filter, and dry to obtain a cerium complex;
[0055] A2. Add 2 g of the cerium complex obtained in step A1, 16 g of lactic acid and 10 g of toluene into a reaction container, react at 140° C. for 2 h, and then evacuate for 4 h with a vacuum degree of 0.05 MPa. After drying, modified PLA-1 is obtained.
[0056] Preparation Example 2
[0057] The preparation method of modified PLA-2 comprises the following steps:
[0058] A1. Dissolve 1 g of cerium nitrate in 8.75 g of deionized water in a reaction container, then add 4 g of monosodium citrate, react at 35° C. for 4 h, add 25 wt % of ammonia water to adjust the pH to 7, let stand for 10 h, centrifuge, filter, and dry to obtain a cerium complex;
[0059] A2. Add 1 g of the cerium complex obtained in step A1, 20 g of lactic acid and 10 g of toluene into a reaction container, react at 140° C. for 2 h, and then evacuate for 4 h with a vacuum degree of 0.05 MPa. After drying, modified PLA-2 is obtained.
[0060] Preparation Example 3
[0061] The preparation method of modified natural cellulose-1 comprises the following steps:
[0062] B1, adding 1 g of cellulose nanocrystals, 2.5 g of isophorone diisocyanate and 0.001 g of tetraisopropyl titanate into a reaction vessel, reacting at 75° C. for 4 h to obtain activated natural cellulose;
[0063] B2. Add 3 g of activated natural cellulose obtained in step B1 and 0.15 g of dopamine into a reaction vessel, react at 35° C. for 1.5 h, add 5 g of tris(hydroxymethyl)aminomethane) buffer with a pH of 8, stir for 22 h, wash the obtained product with deionized water to a pH of 7, filter and dry to obtain modified natural cellulose-1.
[0064] Preparation Example 4
[0065] The preparation method of modified natural cellulose-2 comprises the following steps:
[0066] B1, adding 1 g of cellulose nanocrystals, 2.5 g of isophorone diisocyanate and 0.001 g of tetraisopropyl titanate into a reaction vessel, reacting at 75° C. for 4 h to obtain activated natural cellulose;
[0067] B2. Add 1.5 g of activated natural cellulose obtained in step B1 and 0.15 g of dopamine into a reaction vessel, react at 35° C. for 1.5 h, add 5 g of tris(hydroxymethyl)aminomethane) buffer with a pH of 8, stir for 22 h, wash the obtained product with deionized water to a pH of 7, filter and dry to obtain modified natural cellulose-2.
[0068] Example 1
[0069] A natural cellulose modified degradable oxygen-barrier breathable membrane comprises the following raw materials, measured in parts by weight: 60 parts of modified PLA-1, 12 parts of modified natural cellulose-1, 1.5 parts of epoxidized soybean oil, 3.5 parts of styrene-maleic anhydride-acrylonitrile copolymer, and 1 part of ethylene bisstearamide.
[0070] The method for preparing the degradable oxygen-barrier breathable membrane modified by natural cellulose in this embodiment comprises the following steps:
[0071] S1, after mixing modified PLA-1, modified natural cellulose-1, epoxy soybean oil, styrene-maleic anhydride-acrylonitrile copolymer, and ethylene bisstearic acid amide, adding the mixture into a high-speed mixer and mixing for 25 minutes to obtain a premix;
[0072] S2, putting the premix obtained in step S1 into a twin-screw extruder, and controlling the extrusion temperature at 180° C. to obtain a film blowing masterbatch;
[0073] S3. The film blowing masterbatch obtained in step S2 is blown into a film by a film blowing machine, the screw temperature is controlled at 165° C., the die processing temperature is controlled at 175° C., and the film thickness is 35 μm, to obtain a natural cellulose modified degradable oxygen-barrier breathable film.
[0074] Example 2
[0075] A natural cellulose modified degradable oxygen-barrier breathable membrane comprises the following raw materials, measured in parts by weight: 50 parts of modified PLA-1, 10 parts of modified natural cellulose-1, 1 part of epoxy soybean oil, 2 parts of styrene-maleic anhydride-acrylonitrile copolymer, and 0.1 part of ethylene bisstearamide.
[0076] The method for preparing the degradable oxygen-barrier breathable membrane modified by natural cellulose in this embodiment comprises the following steps:
[0077] S1, after mixing modified PLA-1, modified natural cellulose-1, epoxy soybean oil, styrene-maleic anhydride-acrylonitrile copolymer, and ethylene bisstearamide, adding the mixture into a high-speed mixer and mixing for 20 minutes to obtain a premix;
[0078] S2, putting the premix obtained in step S1 into a twin-screw extruder, and controlling the extrusion temperature at 170° C. to obtain a film blowing masterbatch;
[0079] S3. The film blowing masterbatch obtained in step S2 is blown into a film by a film blowing machine, the screw temperature is controlled at 160° C., the die processing temperature is controlled at 175° C., and the film thickness is controlled to be 35 μm, to obtain a natural cellulose modified degradable oxygen-barrier breathable film.
[0080] Example 3
[0081] A natural cellulose modified degradable oxygen-barrier breathable membrane comprises the following raw materials, measured in parts by weight: 70 parts of modified PLA-1, 15 parts of modified natural cellulose-1, 2 parts of epoxidized soybean oil, 5 parts of styrene-maleic anhydride-acrylonitrile copolymer, and 2 parts of ethylene bisstearamide.
[0082] The method for preparing the degradable oxygen-barrier breathable membrane modified by natural cellulose in this embodiment comprises the following steps:
[0083] S1, after mixing modified PLA-1, modified natural cellulose-1, epoxy soybean oil, styrene-maleic anhydride-acrylonitrile copolymer, and ethylene bisstearic acid amide, adding the mixture into a high-speed mixer and mixing for 30 minutes to obtain a premix;
[0084] S2, putting the premix obtained in step S1 into a twin-screw extruder, and controlling the extrusion temperature at 190° C. to obtain a film blowing masterbatch;
[0085] S3. The film blowing masterbatch obtained in step S2 is blown into a film by a film blowing machine, the screw temperature is controlled at 170° C., the die processing temperature is controlled at 180° C., and the film thickness is 35 μm, to obtain a natural cellulose modified degradable oxygen-barrier breathable film.
[0086] Example 4
[0087] A natural cellulose modified degradable oxygen-barrier breathable membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of modified PLA-1 is replaced by modified PLA-2.
[0088] Example 5
[0089] A natural cellulose-modified degradable oxygen-barrier breathable membrane and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal amount of modified natural cellulose-1 is replaced by modified natural cellulose-2.
[0090] Comparative Example 1
[0091] A natural cellulose-modified degradable oxygen-barrier breathable membrane, the specific implementation manner is the same as that of Example 1, except that an equal amount of modified PLA-1 is replaced by PLA.
[0092] Comparative Example 2
[0093] A natural cellulose-modified degradable oxygen-barrier breathable membrane, the specific implementation manner is the same as that of Example 1, except that an equal amount of modified natural cellulose-1 is replaced by natural cellulose.
[0094] Performance Testing
[0095] The biodegradable oxygen-barrier breathable membranes modified with natural cellulose obtained in the above-mentioned embodiments and comparative examples were tested:
[0096] (1) Mechanical properties: The tensile strength of the natural cellulose modified biodegradable oxygen barrier breathable membrane was measured according to GB / T1040.2-2006.
[0097] (2) Tear resistance: The tear strength of the natural cellulose modified degradable oxygen barrier breathable film was measured according to JIS K7128-3:1998.
[0098] (3) Antibacterial performance: The antibacterial performance of the natural cellulose modified degradable oxygen barrier breathable membrane was measured by using the plate colony counting method to test the antibacterial activity of the natural cellulose modified degradable oxygen barrier breathable membrane against Escherichia coli. All natural cellulose modified degradable oxygen barrier breathable membranes were cut into circular specimens with a diameter of 10 mm and placed at the bottom of a 24-well plate. Subsequently, 100 μL of the diluted bacterial suspension (approximately 10 5CFU / mL), and evenly dispersed on the surface of the membrane. Then put the 24-well plate into a bacterial incubator and culture it at 37°C for 6 hours. Then, take out each sample and soak it in a test tube containing 10mL of PBS solution, then shake all the test tubes in a water bath thermostat oscillator (150rpm) for 10 minutes. Subsequently, 60μL of the diluted bacterial suspension was spread on a nutrient agar plate, cultured at 37°C for 24h, and the number of viable colonies was counted, and the experiment was repeated three times to take the average value.
[0099] (4) Oxygen barrier performance: The oxygen transmission rate was tested using a VACV1 oxygen transmission rate tester at a temperature of 23°C and a relative humidity of 0%.
[0100] The test results are shown in Table 1:
[0101] Table 1
[0102]
[0103]
[0104] It can be seen from the data in Table 2 that the degradable oxygen barrier breathable membrane modified by natural cellulose in Examples 1-3 of the present invention has good mechanical properties, tear resistance, antibacterial properties and oxygen barrier properties. From the comparison between Example 4 and Example 1, it can be seen that the various properties of the degradable oxygen barrier breathable membrane modified by natural cellulose are reduced after changing the content of lactic acid; from the comparison between Example 5 and Example 1, it can be seen that after changing the content of activated natural cellulose, the mechanical properties, tear resistance and antibacterial properties of the degradable oxygen barrier breathable membrane become worse; from the comparison between Comparative Examples 1 and 2 and Example 1, it can be seen that the performance of the degradable oxygen barrier breathable membrane with the addition of unmodified PLA or unmodified natural cellulose is poor.
[0105] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A biodegradable oxygen-barrier breathable membrane modified from natural cellulose, characterized in that: The composition comprises the following raw materials in parts by weight: 50-70 parts of modified PLA, 10-15 parts of modified natural cellulose, 1-2 parts of plasticizer, 2-5 parts of compatibilizer, and 0.1-2 parts of lubricant; The preparation method of the modified PLA comprises the following steps: A1. Dissolve cerium nitrate in deionized water in a reaction vessel, then add a complexing agent, react at 30-40° C. for 3-5 hours, add 20-28 wt % ammonia water to adjust the pH to 7-8, let stand for 8-12 hours, centrifuge, filter, and dry to obtain a cerium complex; A2, adding the cerium complex obtained in step A1, lactic acid and solvent into a reaction vessel, reacting at 130-150° C. for 1-3 h, and then evacuating for 3-5 h with a vacuum degree of 0-0.1 MPa, and obtaining modified PLA after drying; The mass ratio of the cerium complex to lactic acid in step A2 is 1:(7-8).
2. The natural cellulose modified degradable oxygen barrier breathable membrane according to claim 1, characterized in that: The complexing agent is one or more of monosodium citrate, monosodium malate and sodium hydrogen tartrate.
3. The natural cellulose modified degradable oxygen barrier breathable membrane according to claim 1, characterized in that: The method for preparing the modified natural cellulose comprises the following steps: B1, adding natural cellulose, isophorone diisocyanate and organic bismuth into a reaction vessel, reacting at 70-80° C. for 3-5 hours to obtain activated natural cellulose; B2. Add the activated natural cellulose and dopamine obtained in step B1 to a reaction vessel, react at 30-40° C. for 1-2 hours, add tris(hydroxymethyl)aminomethane buffer with a pH of 8-9, stir for 20-24 hours, wash the obtained product with deionized water to a pH of 7-8, filter and dry to obtain modified natural cellulose.
4. The natural cellulose modified degradable oxygen barrier breathable membrane according to claim 3, characterized in that: The mass ratio of activated natural cellulose and dopamine in step B2 is (15-25):
1.
5. The natural cellulose modified degradable oxygen barrier breathable membrane according to claim 3, characterized in that: The natural cellulose is one or more of bamboo fiber, hemp fiber, microcrystalline cellulose, cellulose nanocrystal, and wool.
6. The natural cellulose modified degradable oxygen barrier breathable membrane according to claim 1, characterized in that: The plasticizer is one or more of epoxy fatty acid, epoxy soybean oil, citrate, polyethylene glycol, and castor oil derived ester.
7. The natural cellulose modified degradable oxygen barrier breathable membrane according to claim 1, characterized in that: The lubricant is pentaerythritol stearate or ethylene bis stearamide.
8. A method for preparing the natural cellulose modified degradable oxygen barrier breathable membrane according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. After mixing modified PLA, modified natural cellulose, plasticizer, compatibilizer and lubricant, add them into a high-speed mixer and mix for 20-30 minutes to obtain a premix; S2, putting the premix obtained in step S1 into a twin-screw extruder, and controlling the extrusion temperature at 170-190° C. to obtain a film blowing masterbatch; S3. The film blowing masterbatch obtained in step S2 is blown into a film by a film blowing machine, the screw temperature is controlled at 160-170° C., the die processing temperature is controlled at 170-180° C., and the film thickness is controlled at 25-50 μm to obtain a natural cellulose modified degradable oxygen-barrier breathable film.
Citation Information
Patent Citations
A polylactic acid grafted modified natural fiber and PLA composite material and its preparation method
CN111825845B
Modified cellulose-filled PBAT / PLA composition suitable for preparing film as well as preparation and application of modified cellulose-filled PBAT / PLA composition
CN112552655A
High-barrier biodegradable material, and preparation method and application thereof
CN113861643A